Cardio-metabolic responses during horse riding at three different speeds - Sainas, G.; Melis, S.; Corona, F.; Loi, A.; Ghiani, G.; Milia, R.; Milia, R.; Tocco, F.; Marongiu, E.; Crisafulli, A. (European Journal of Applied Physiology, 2016)
Purpose: The purpose of the present investigation was to study the metabolic demand and cardiovascular response during a typical horse riding session. Methods: To this aim, 19 (9 male, 10 female) riders, regularly participating in competitions, were enrolled. They underwent a preliminary, incremental exercise test on a cycle-ergometer to assess their anaerobic threshold (AT) and VO2max. Then, participants underwent a riding training session, which comprised periods of walking, trotting, and cantering for a total of 20 min. Oxygen uptake (VO2), carbon dioxide production (VCO2), and heart rate (HR) were obtained throughout the preliminary and riding test by means of a portable metabolic system. Moreover, excess of CO2 production (CO2excess) and oxygen pulse (OP) were also calculated to obtain an estimate of anaerobic glycolysis and stroke volume. Results: The main result was that all collected parameters remained below the AT level throughout the riding session, with the exception of HR that approached the AT level only during cantering. In detail, during cantering, average VO2, VCO2, HR, CO2excess, and OP values were 1289 ± 331 mL min-1, 1326 ± 266 mL min-1, 158 ± 22 bpm, 215 ± 119 mL min-1, and 7.8 ± 1.6 mL/bpm, respectively. Conclusions: It was concluded that riding imposes only light to moderate stress on the aerobic and anaerobic energy systems. Moreover, cardiovascular reserve is only moderately recruited in terms of inotropism, while chronotropism can be stimulated more.